REFLECTIONS ON A TEACHER-LED CPD MODEL FOR EFL TEACHERS - Bayram, İlknur and Canaran, Özlem (International Online Journal of Education and Teaching, 2018)
This qualitative case study aims to explore EFL teachers’ reflections of a teacher-led continuous professional development model conducted at the department of foreign languages of a privately funded university. It also aims to find out what implications this model might have for the professional development of teachers. Data for the study was collected through observations, focus group interviews, document analysis and an evaluation survey. Results of the study which was carried out during four academic terms (2015-2017) reveal that teachers reflected mostly on the process of the model, its implications for their professional development and offered suggestions for future CPD practices. Keywords: EFL Teachers, Teacher-led Professional Development, Qualitative Case Study